KEKERASAN SIMBOLIK MEDIA ONLINE (Analisis Framig Berita Fenomena LGBT dalam Portal Berita Republika Online) - Eunike Cahya Utaminingtyas (Interaksi Online, 2017)
Online media is the latest form of mass media which have the ability to dominate a value and form public perception. Media’s ability to form this public perception is also done by highlighting Lesbian, Gay, Bisexual and Transgender (LGBT) community in Indonesia. Media did not only construct reality on LGBT phenomenon, but also create symbolic violence with order of words in its news texts. Normatively, media has responbility to report LGBT news that cover both sides and does not discriminative. The purpose of this research is to describe the frame carried by Republika Online on LGBT phenomenon news as form of symbolic violence in media. This research uses Queer Theory and some concepts of symbolic violence in the media. Critical constructivism paradigm and text analysis method of framing model of Zhondang Pan and Gerald M. Kosciki were used to analyze the data. The result shows that Republika Online constructed LGBT phenomenon reality with sociology frame that described LGBT as a social disease and provide the description as suspect in their news. Form of symbolic violence are found on all four framing structures: 1) Syntactic Structure by framing information which found in quotation and news source 2) Script Structure by telling LGBT phenomenon in one perspective which found on how and why 3) Thematic Structure by writing information detail on counter perspective 4) Rhetoric Structure by emphasizing negative tone on LGBT phenomenon information which found on choice of words and methaphor. Other findings was Republika Online did domination of value as form of symbolic violence by monopoly of information by doing euphimization and censorship that gives no room for pro-LGBT views. Element of sexuality was empashized in news on LGBT phenomenon that is only made for media commodities.